The Effect Of Job Satisfaction And Compensation On Performance Of Employees In Multinational Automotive Company - Imam Jayanto; Fatkhuri Fatkhuri; Eka Kurnia Saputra; Samuel PD Anantadjaya; Irma M. Nawangwulan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Employee performance is individual because each employee has a different level of ability in carrying out their duties. Performance depends on a combination of abilities, efforts, and opportunities that are obtained. This study aims to see how much the influence of compensation and job satisfaction together on the performance of employees of PT. ASTRA International Tbk - Daihatsu partially and simultaneously. In this study, the type of research used is associative research. Where the writer tries to know the relationship between two variables partially or simultaneously. This study's method of collecting data used a questionnaire with multiple linear regression analysis methods. The results of the study show that partial compensation and job satisfaction affect the performance of employees at PT. ASTRA International Tbk - Daihatsu. Simultaneously partial compensation and job satisfaction affect the performance of employees of PT. ASTRA International Tbk – Daihatsu with a contribution of 65.9%.